Anger and long-term mortality and ventricular arrhythmias in patients with a first-time implantable cardioverter-defibrillator: data from the MIDAS study. Issue 7 (19th May 2020) - Pedersen, Susanne S; Andersen, Christina Maar; Burg, Matthew; Theuns, Dominic A M J
Abstract: Aims: Psychosocial factors increase risk for incident heart disease and poor prognosis. In patients with an implantable cardioverter-defibrillator (ICD), negative emotions have been associated with increased mortality risk, although the association with ventricular arrhythmias (VAs) is less consistent. Anger has been linked to incident ICD shocks, but no prospective study has examined the association of anger (state and trait) with mortality or VAs in the ICD population. In a consecutively recruited cohort of first-time ICD patients, we examined the association of state and trait anger with 7-year mortality risk and time to first VA. Methods and results: A consecutive cohort of patients implanted with a first-time ICD ( n  = 388; 80% men) between 2003 and 2010 completed the State-Trait Anger Scale and were followed for 7 years. Outcomes were mortality and time to first appropriate ICD therapy. State anger at the time of implant was associated with increased mortality risk in adjusted analyses, with a 1-point increase in score on the state anger measures associated with a 5% [hazard ratio 1.05; 95% confidence interval 1.01–1.09; P  =   0.015] increased 7-year mortality risk. We found no statistically significant differences in mortality risk for trait anger, nor an effect for state or trait anger on time to first treated VA (all ps > 0.05). Conclusion: This is the first study to examine the association of state and trait anger with long-term clinical outcomes in ICD patients. Evaluating anger reduction strategies in newly implanted ICD patients, such as self-regulation or mindfulness techniques, may be warranted for reducing mortality risk.